2021
DOI: 10.1016/j.immuni.2021.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 produced by enteric neurons regulates the number and phenotype of microbe-responsive regulatory T cells in the gut

Abstract: Highlights d Treg cells in the colon lamina propria reside close to neuron projections d Neurons modulate the differentiation and phenotype of iTreg cells in culture via IL-6 d Neuron-specific ablation of Il6 increases the number of RORg + Treg cells in vivo d Microbial colonization affects a subset of neurons in the enteric nervous system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 77 publications
(123 reference statements)
1
65
0
Order By: Relevance
“…However, a subset of pTreg cells that is induced in the gut and co-expresses Foxp3 and ROR-γt to regulate immune responses to commensal bacteria is dependent on IL-6. In fact, Il6 –/– mice exhibit significantly reduced fractions of ROR-γt + Treg cells in the gut lamina propria [54] , and a very recent report suggests that enteric neurons are a relevant source of IL-6 for the induction of ROR-γt + Treg cells [55] . ROR-γt + Treg cells and Th17 cells share similar cytokine cues for their development, yet are differentially dependent on vitamine A, which promotes Treg induction but not Th17 cell development [54] .…”
Section: Sensing Of Il-6 By Treg Cellsmentioning
confidence: 99%
“…However, a subset of pTreg cells that is induced in the gut and co-expresses Foxp3 and ROR-γt to regulate immune responses to commensal bacteria is dependent on IL-6. In fact, Il6 –/– mice exhibit significantly reduced fractions of ROR-γt + Treg cells in the gut lamina propria [54] , and a very recent report suggests that enteric neurons are a relevant source of IL-6 for the induction of ROR-γt + Treg cells [55] . ROR-γt + Treg cells and Th17 cells share similar cytokine cues for their development, yet are differentially dependent on vitamine A, which promotes Treg induction but not Th17 cell development [54] .…”
Section: Sensing Of Il-6 By Treg Cellsmentioning
confidence: 99%
“…Such potential strategies could include overexpression of FOXP3 as aforementioned, or the knockout of molecules involved in pro-inflammatory signaling pathways present in inflamed tissues of autoimmunity. Notably, although the underlying mechanisms of Treg deficiencies in many AID are not well understood, human studies have reported that cytokines like IL-12 and IL-6 can induce defective Treg functions in vitro (19,134). Hence, ablation of receptors that bind these cytokines might avoid pathological Treg instability following adoptive transfer.…”
Section: Challenges and Improvements Of Antigen-specific Treg Therapiesmentioning
confidence: 99%
“…In particular, glial cell-derived neurotrophic factor secreted by EGC is involved in the regulation of ILC3, which are a component of the glial–ILC3–epithelial cell unit that surveys gut environment and control its defence ( 11 ). In a recent study, Yan and co-authors demonstrated that enteric neurons themselves can exert a key role in the regulation of immune cells, by preventing microbial-induced differentiation of regulatory T (Treg) cells through the release of IL-6 ( 12 ).…”
Section: What Is the Gut-brain Axis?mentioning
confidence: 99%